The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1462-2920.2012.02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Sinorhizobium meliloti glutaredoxins regulate iron metabolism and symbiotic bacteroid differentiation

Abstract: Summary Legumes interact symbiotically with bacteria of the Rhizobiaceae to form nitrogen‐fixing root nodules. We investigated the contribution of the three glutaredoxin (Grx)‐encoding genes present in the Sinorhizobium meliloti genome to this symbiosis. SmGRX1 (CGYC active site) and SmGRX3 (CPYG) recombinant proteins displayed deglutathionylation activity in the 2‐hydroethyldisulfide assay, whereas SmGRX2 (CGFS) did not. Mutation of SmGRX3 did not affect S. meliloti growth or symbiotic capacities. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 71 publications
2
36
0
Order By: Relevance
“…In this regard both GroEL and DnaK1 (two chaperones that are essential for heat adaptation) were also identified as GrxA targets (Li et al, 2007), which suggests that GrxA could be needed for activation or as a helper of both chaperones to function in response to heat shock. Similar phenotypes with respect to oxidative stress sensitivity and heat shock sensitivity have been reported for glutaredoxin mutants in other bacteria (Prinz et al, 1997; Fernandes and Holmgren, 2004; Li et al, 2004b; Benyamina et al, 2013) and in yeast (Luikenhuis et al, 1998; Draculic et al, 2000; Chung et al, 2004), suggesting that dithiolic glutaredoxins could have conserved roles in microorganisms. Finally, we have tested whether SGRXA strains were sensitive to metals and selenium compounds.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this regard both GroEL and DnaK1 (two chaperones that are essential for heat adaptation) were also identified as GrxA targets (Li et al, 2007), which suggests that GrxA could be needed for activation or as a helper of both chaperones to function in response to heat shock. Similar phenotypes with respect to oxidative stress sensitivity and heat shock sensitivity have been reported for glutaredoxin mutants in other bacteria (Prinz et al, 1997; Fernandes and Holmgren, 2004; Li et al, 2004b; Benyamina et al, 2013) and in yeast (Luikenhuis et al, 1998; Draculic et al, 2000; Chung et al, 2004), suggesting that dithiolic glutaredoxins could have conserved roles in microorganisms. Finally, we have tested whether SGRXA strains were sensitive to metals and selenium compounds.…”
Section: Discussionsupporting
confidence: 66%
“…Class IV is restricted to photosynthetic eukaryotes and class III is specific to land plants. On the other hand class VI seems to be restricted to cyanobacteria and class V is only present in cyanobacteria and some proteobacteria (Benyamina et al, 2013). In photosynthetic eukaryotes the repertoire of glutaredoxin proteins is larger than in other organisms, which suggests that they could play critical roles regulating processes related to photosynthesis (Rouhier et al, 2008; Couturier et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…An in silico analysis of the S. meliloti genome led to the identification of three genes that putatively encode Grxs from different classes ( Figure 2 ): Grx1, containing the dithiol CGYC active site of class I Grxs; Grx2, containing the monothiol CGFS active site of class II Grxs; and Grx3, carrying two domains, an N-terminal Grx domain with a CPYG active site and a C-terminal domain with a methylamine utilization protein motif (Benyamina et al, 2013). Inactivation of one gene or the other showed that Grx1 and Grx2 play different roles, Grx1 in protein deglutathionylation and Grx2 in regulation of iron metabolism.…”
Section: Thiol-based Redox Regulatory Network In Bacteroidsmentioning
confidence: 99%
“…We conclude that S. meliloti needs SufT to produce sufficient amounts of Fe/S proteins during symbiosis. A decrease in symbiotic performance possibly linked to Fe/S cluster metabolism has also been reported for an S. meliloti mutant lacking the monothiol glutaredoxin SmGRX2, which is attenuated in nitrogen fixation capacity (63). Monothiol glutaredoxins have been suggested to serve for delivery of [2Fe-2S] clusters in some bacteria and eukaryotes (23).…”
Section: Discussionmentioning
confidence: 99%
“…The gshB1 mutant displays early senescence of bacteroids (64). SmGRX1 contributes to protein deglutathionylation, and its null mutant is defective in nodule development and bacteroid differentiation (63). The expression of rpoH1 and several RpoH-regulated genes, including sufT and grxC, is increased by NCR peptides (65,66), suggesting that these genes are incorporated into a complex regulatory network that allows bacteria to adapt to the host cell environment.…”
Section: Discussionmentioning
confidence: 99%